2014
DOI: 10.4103/0972-2327.128571
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba meningoencephalitis

Abstract: Report of a case of young immunocompetent male adult with autopsy proven acanthamoeba meningoencephalitis. The patient presented with a protracted febrile illness of 3 months duration with features of meningoencephalitis, this was followed by rapid deterioration while on anti tuberculous therapy and steroids and ended fatally. His magnetic resonance imaging showed features of hemorrhagic meningoencephalitis and magnetic resonance spectroscopy showed choline peak. Autopsy revealed necrotizing meningoencephaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The enhancement pattern of the largest lesion evolved over time: initially focal and asymmetric eventually becoming a peripheral thin rim. This would confirm an inflammatory zone that has been previously shown histologically to correlate with an inflammatory response secondary to amoebic trophozoite infiltration of the pial vessels and a border zone encephalitis [ 9 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The enhancement pattern of the largest lesion evolved over time: initially focal and asymmetric eventually becoming a peripheral thin rim. This would confirm an inflammatory zone that has been previously shown histologically to correlate with an inflammatory response secondary to amoebic trophozoite infiltration of the pial vessels and a border zone encephalitis [ 9 ].…”
Section: Discussionsupporting
confidence: 82%
“…Acanthamoeba is traditionally described as affecting the posterior structures of the brain [ 7 ]. However, as in our case, which initially affected the left temporal lobe, reported cases have been described in various brain lobes and brainstem structures often with an associated meningoencephalitis [ 7 9 ]. With worsening infection, eventually the signs of raised intracranial pressure develop invariably leading to coma and death.…”
Section: Discussionmentioning
confidence: 53%
“…In this case, the patient was immunocompetent. Conditions predisposing include diabetes mellitus, splenectomy, hypoalbuminemia, renal failure, bone marrow failure, lymphoproliferative, hematoproliferative disorders, splenectomy, hypoproteinemia, corticosteroid use, immunomodulatory drug use, chemotherapy, and HIV infection [6]. It has also been reported in immunocompetent individuals from low socioeconomic status [7].…”
Section: Discussionmentioning
confidence: 99%
“…This is explained by the belief that amoebae can migrate along corneal nerves [30]. Chandra et al [15] described the case of a patient with a normal immune response diagnosed with meningitis caused by…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Acanthamoeba keratitis found that the host immune system prevents the spread of amoebae into the eyeball and other organs through the recruitment of neutrophils [12][13][14]. However, there is some data showing infection of the eyeball in hosts with disseminated acanthamoebiasis [15].…”
Section: Acanthamoeba Including a Castellanii A Polyphaga A Hatmentioning
confidence: 99%